Bung Sultan Bunga rampai esai tentang lelaku priyayi Jawa R.P.A. Suyanto Sastroatmodjo ; penyunting, R. Toto Sugiharto. - SUYANTO SASTROATMODJO, R.P.A.; Toto Sugiharto, R. (Adiwacana, 2008)
xxxiv, 230 hlm. 21 cm (3 eks.)